2011
DOI: 10.1038/nmat3200
|View full text |Cite
|
Sign up to set email alerts
|

Second-harmonic generation in silicon waveguides strained by silicon nitride

Abstract: Silicon photonics meets the electronics requirement of increased speed and bandwidth with on-chip optical networks. All-optical data management requires nonlinear silicon photonics. In silicon only third-order optical nonlinearities are present owing to its crystalline inversion symmetry. Introducing a second-order nonlinearity into silicon photonics by proper material engineering would be highly desirable. It would enable devices for wideband wavelength conversion operating at relatively low optical powers. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
291
2
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 308 publications
(313 citation statements)
references
References 31 publications
12
291
2
1
Order By: Relevance
“…As recently shown, non-vanishing Pockels coefficients are induced in Silicon if strain-gradients are present 18,28 . However, Si remains non-ferroelectric and thus no effects of poling are visible, in clear contrast to our observations.…”
Section: Articlementioning
confidence: 83%
“…As recently shown, non-vanishing Pockels coefficients are induced in Silicon if strain-gradients are present 18,28 . However, Si remains non-ferroelectric and thus no effects of poling are visible, in clear contrast to our observations.…”
Section: Articlementioning
confidence: 83%
“…with a strained silicon nitride overlay. As such a silicon pockets effect modulator [69] and second harmonic generation [70] has been demonstrated in a silicon waveguide. Another approach for enhancing the nonlinear response of silicon waveguides is by making use of the strong photon-phonon coupling that can be achieved in these waveguides using stimulated Brillouin scattering.…”
Section: Non-kerr Nonlinearities In Siliconmentioning
confidence: 99%
“…Nevertheless, a signicant amount of research activities have demonstrated promising strategies to boost optical nonlinearities in Si-based materials systems. Recently, enhanced secondorder nonlinearity in Si has been demonstrated by a number of approaches including higher-order multipolar processes, 5 the breaking of crystal symmetry at interfaces, the engineering of strain elds, [6][7][8][9][10][11][12] or the development of substoichiometric silicon nitride thin lms. 13 An alternative strategy relies on the integration atop Si technology of non-centrosymmetric semiconductor nanostructures that feature very efficient optical nonlinear coefficients, thus potentially enabling a number of novel device applications.…”
Section: Introductionmentioning
confidence: 99%
“…Data have to be compared with efficiencies reported in literature from other nanostructures. 12,13,[40][41][42][43] The measured efficiency for the bulk InAs bulk substrate is reported as a reference. The SH enhancement due to the nano-wing shaped samples is measured and it features a maximum enhancement of the SH generation of approximately a factor 500 for the thinnest (72 nm) and shortest (475 nm) nanostructures.…”
mentioning
confidence: 99%